Efficacy and safety of melflufen plus daratumumab and dexamethasone in relapsed/refractory multiple myeloma: results from the randomized, open-label, phase III LIGHTHOUSE study - Pour, Luděk; Szarejko, Monika; Bila, Jelena; Schjesvold, Fredrik H; Spicka, Ivan; Maisnar, Vladimir; Jurczyszyn, Artur; Grudeva-Popova, Zhanet; Hájek, Roman; Usenko, Ganna; Thuresson, Marcus; Norin, Stefan; et al. (Haematologica, 2024)
Melphalan flufenamide (melflufen), a first-in-class alkylating peptide-drug conjugate, plus dexamethasone was approved in Europe for use in patients with triple-class refractory relapsed/refractory multiple myeloma (RRMM) with ≥3 prior lines of therapy and without prior autologous stem cell transplantation (ASCT) or with a time to progression >36 months after prior ASCT. The randomized LIGHTHOUSE study (NCT04649060) assessed melflufen plus daratumumab and dexamethasone (melflufen group) versus daratumumab in patients with RRMM with disease refractory to an immunomodulatory agent and a proteasome inhibitor or who had received ≥3 prior lines of therapy including an immunomodulatory agent and a proteasome inhibitor. A partial clinical hold issued by the US Food and Drug Administration for all melflufen studies led to financial constraints and premature study closure on February 23rd 2022 (data cut-off date). In total, 54 of 240 planned patients were randomized (melflufen group, N=27; daratumumab group, N=27). Median progression-free survival (PFS) was not reached in the melflufen group versus 4.9 months in the daratumumab group (Hazard Ratio: 0.18 [95% Confidence Interval, 0.05-0.65]; P=0.0032) at a median follow-up time of 7.1 and 6.6 months, respectively. Overall response rate (ORR) was 59% in the melflufen group versus 30% in the daratumumab group (P=0.0300). The most common grade ≥3 treatment-emergent adverse events in the melflufen group versus daratumumab group were neutropenia (50% vs. 12%), thrombocytopenia (50% vs. 8%), and anemia (32% vs. 19%). Melflufen plus daratumumab and dexamethasone demonstrated superior PFS and ORR versus daratumumab in RRMM and a safety profile comparable to previously published melflufen studies.
Keywords: Proteasome Inhibitors; dexamethason; monoklonální protilátky; Antineoplastic Combined Chemotherapy Protocols; inhibitory proteasomu; nádory plazmocelulární; transplantace hematopoetických kmenových buněk; neutropenie; fenylalanin; Dexamethasone; Phenylalanine; Multiple Myeloma; melfalan; autologní transplantace; Neutropenia; lidé; United States; Humans; protokoly protinádorové kombinované chemoterapie; Transplantation, Autologous; Spojené státy americké; Antibodies, Monoclonal; mnohočetný myelom; Melphalan; Neoplasms, Plasma Cell; Hematopoietic Stem Cell Transplantation